The Potential of Donor T-Cell Repertoires in Neoantigen-Targeted Cancer Immunotherapy - Karpanen, Terhi; Olweus, Johanna (Frontiers in Immunology, 2017)
T cells can recognize peptides encoded by mutated genes, but analysis of tumor-infiltrating lymphocytes suggests that very few neoantigens spontaneously elicit T-cell responses. This may be an important reason why immune checkpoint inhibitors are mainly effective in tumors with a high mutational burden. Reasons for clinically insufficient responses to neoantigens might be inefficient priming, inhibition, or deletion of the cognate T cells. Responses can be dramatically improved by cancer immunotherapy such as checkpoint inhibition, but often with temporary effects. By contrast, T cells from human leukocyte antigen (HLA)-matched donors can cure diseases such as chronic myeloid leukemia. The therapeutic effect is mediated by donor T cells recognizing polymorphic peptides for which the donor and patient are disparate, presented on self-HLA. Donor T-cell repertoires are unbiased by the immunosuppressive environment of the tumor. A recent study demonstrated that T cells from healthy individuals are able to respond to neoantigens that are ignored by tumor-infiltrating T cells of melanoma patients. In this review, we discuss possible reasons why neoantigens escape host T cells and how these limitations may be overcome by utilization of donor-derived T-cell repertoires to facilitate rational design of neoantigen-targeted immunotherapy.